Nasal Polyposis: Current Trends - Rajguru, Renu (Springer India, 2011)
Nasal polyps (NP) are one of the most common inflammatory mass lesions of the nose, affecting up to 4% of the population. They present with nasal obstruction, anosmia, rhinorrhoea, post nasal drip, and less commonly facial pain. Their etiology remains unclear, but they are known to have associations with allergy, asthma, infection, fungus, cystic fibrosis, and aspirin sensitivity. However, the underlying mechanisms interlinking these pathologic conditions to NP formation remain unclear. Also strong genetic factors are implicated in the pathogenesis of NP, but genetic and molecular alterations required for its development and progression are still unclear. Management of NP involves a combination of medical therapy and surgery. There is good evidence for the use of corticosteroids (systemic and topical) both as primary treatment and as postoperative prophylaxis against recurrence, but the prolonged course of the disease and adverse effects of systemic steroids limits their use. Hence several new drugs are under trial. Surgical treatment has been refined significantly over the past 20 years with the advent of endoscopic sinus surgery and, in general, is reserved for cases refractory to medical treatment. Recurrence of the polyposis is common with severe disease recurring in up to 10% of patients. Over the last two decades, increasing insights in the pathophysiology of nasal polyposis opens perspective for new pharmacological treatment options, with eosinophilic inflammation, IgE, fungi and Staphylococcus aureus as potential targets. A better understanding of the pathophysiology underlying the persistent inflammatory state in NP is necessary to ultimately develop novel pharmacotherapeutic approaches. In this paper we present the newer treatment options available for better control and possibly cure of the disease.